Thrombus composition and its implication in ischemic stroke assessment and revascularization treatments - Juan Marta-Enguita; Florencio J.D. Machado; Josune Orbe; Roberto Muñoz (Neurología (English Edition))
Introduction: Since mechanical thrombectomy has allowed ischaemic stroke thrombus retrieval, the exhaustive study of this material has enabled better understanding of the potential physiopathological processes involved in thrombus formation. Development: Thrombotic pathways involved in the different vascular beds share common mechanisms, causing difficulties in the identification of specific patterns associated with stroke aetiology. However, other factors such as clot formation time, associated inflammatory status, or activation of additional immune and coagulation pathways (neutrophil extracellular trap [NET] delivery, platelet aggregation, endothelial activation, and von Willebrand Factor release) have been described as determinants in thrombus characteristics. Thus, variable proportions of fibrin-/platelet-rich and erythrocyte-rich areas are closely interrelated within the thrombus, frequently associated with a protective outer shell with high concentrations of fibrin, NETs, and von Willebrand Factor. The presence of these components, as well as their distribution and interrelationships, have been shown to have effects on the thrombus’ resistance to revascularisation treatments. Understanding of these pathways has enabled the development of adjuvant therapies capable of enhancing current fibrinolytic drugs and/or increasing the efficacy of endovascular treatments. Conclusion: Understanding of thrombus components and mechanisms involved in thrombus formation represent a potential pathway for the development of ischaemic stroke therapeutics with promising perspectives. Resumen: Introducción: La obtención del material trombótico en el ictus isquémico desde la generalización de la trombectomía mecánica ha permitido un estudio exhaustivo del mismo y de los posibles mecanismos fisiopatológicos subyacentes a su formación. Desarrollo: Los mecanismos trombóticos implicados en los diferentes lechos vasculares no difieren en exceso, condicionando una heterogeneidad importante que ha dificultado la identificación de patrones asociados al origen o etiología del ictus. Se ha observado sin embargo una mayor influencia de factores como el tiempo de desarrollo del coágulo, el estado inflamatorio sistémico o la activación de vías inmunes y de la coagulación [liberación de Neutrophil extracellular traps (NETs), agregación plaquetar, activación endotelial y liberación de Factor de vonWillebrand]. Como resultado, en el seno del trombo conviven en proporciones variables áreas ricas en eritrocitos y áreas ricas en plaquetas/fibrina con una íntima relación entre ellas y acompañadas con frecuencia de una coraza protectora con alto contenido en fibrina, Factor vonWillebrand y NETs. La presencia de estos componentes, así como su disposición e interrelación ha demostrado tener efectos en la resistencia a los diferentes tratamientos revascularizadores. El conocimiento de estas vías ha permitido el desarrollo de posibles terapias adyuvantes con capacidad de potenciar los tratamientos fibrinolíticos actuales y/o aumentar la eficacia del tratamiento endovascular. Conclusión: El conocimiento de los componentes del trombo y los posibles mecanismos implicados en su formación es una potencial vía de desarrollo en el tratamiento del ictus isquémico con resultados prometedores.